Vertebrate microremains from the Lower Silurian of Siberia and Central Asia: palaeobiodiversity and palaeobiogeography - žigaitė, živilė; Karatajūtė-Talimaa, Valentina; Blieck, Alain (Journal of Micropalaeontology, 2011)
The biostratigraphic and palaeogeographical distributions of early vertebrate microfossils from a number of Lower Silurian localities in northwestern Mongolia, Tuva and southern Siberia were reviewed. Vertebrate microremains showed high taxonomic diversity, comprising acanthodians, chondrichthyans, putative galeaspids, heterostracans, mongolepids, tesakoviaspids, thelodonts and possible eriptychiids. The majority of taxa have lower stratigraphic levels of occurrence compared to other Silurian palaeobiogeographical provinces, such as the European-Russian or Canadian Arctic. Vertebrate microremains are numerous within the samples, which may indicate warm-water low-latitude palaeobasins with rich shelf faunas. This disagrees with the recent interpretations of the territory as a northern high-latitude Siberian palaeocontinent. The palaeobiogeographical distribution of vertebrate taxa indicates an endemic palaeobiogeographical province of connected epeiric palaeoseas with external isolation during the early Silurian. In previous works separation between Tuvan and Siberian palaeobiogeographical provinces has been suggested. After careful revision of the vertebrate microfossil record of the region, we find that differences in a few vertebrate taxa do not provide not strong enough evidence to reliably distinguish these provinces. We therefore dispute the hypothesis of two biogeographical provinces in the early Silurian of the Siberian palaeocontinent, and propose a single unified Siberian–Tuvan palaeobiogeographical province.